Sensory perception of meat from entire male pigs processed by different heating methods. (December 2017) - Peñaranda, Irene; Garrido, Ma Dolores; Egea, Macarena; Díaz, Pedro; Álvarez, Daniel; Oliver, Ma Angeles; Linares, Ma Belén
Abstract: The aim of this study was to evaluate the perception of androstenone in pork from entire male pigs with different androstenone levels (High ≥ 2 mg kg − 1 ; Medium 0.5–0.7 mg kg − 1 ) applying four different heating methods (vacuum, grill, oven and frying). Androstenone (AND) perception was analysed during and after cooking by a trained panel. During cooking, the highest score for AND odour (greatest perception) was obtained with the grill and vacuum, while frying was the best option for reducing its perception, which was judged to be imperceptible for androstenone medium level (P < 0.05). In cooked samples, there were level, heating method and its interaction effects for AND odour and flavour, meat flavour, juiciness and hardness (P < 0.05). The samples treated by vacuum and frying had a proper texture profile. However the frying method provided the lowest score in AND perception, making it the best option for reducing both AND odour and flavour. In short, the use of different heating methods strongly affected AND perception. Highlights: Odour perception during cooking is reduced by frying method. Frying method reduces AND odour and flavour on medium and high meat samples. Vacuum method obtained the highest punctuation for AND odour and flavour. Texture attributes were improved by frying system in leaner samples.